Root surface conditioning with nicotine or cotinine reduces viability and density of fibroblasts in vitro - Martinez, AET; Silverio, K. G.; Fogo, J. C.; Kirkwood, K. L.; Rossa, C. (Springer, 2005)
The purpose of study was to evaluate fibroblast attachment and cellular morphology on root surfaces chemically conditioned with nicotine or cotinine. A secondary objective was to determine if mechanical scaling and root planning of these chemically conditioned surfaces would alter cellular attachment. Root surface dentin specimens were prepared from uniradicular teeth of non-smoking patients. Specimens were randomly assigned to two experimental groups: no treatment (chemical conditioning only) and scaling and root planning after conditioning (SRPC). The concentrations of the tested substances were in the range of 0-1 mg/mL (nicotine) and 0-1 ?g/mL (cotinine). After a 24-h conditioning period, dentin slices were incubated with continuous lineage of fibroblastic cells from rat (McCoy cells) for another 24 h. Specimens were prepared for SEM analysis and microphotographs. The statistical analysis of the data indicated significant alteration of cellular morphology on fibroblasts that were grown on root surface exposed to nicotine concentrations greater than 1 ? g/mL. This effect of nicotine was not reduced by SRPC. on the other hand, in the SRPC group cellular density was greater. For cotinine-conditioned specimens, the greater concentrations also led to alteration on morphology, and these alterations were observed in the SRPC group as well. Cotinine did not induce significant changes on cellular density. The results indicated that fibroblasts are negatively influenced by nicotine present on the dentin substrate and also that scaling may reduce these effects. Cotinine treatment on root surfaces may alter cell morphology and density but these effects were less severe than that promoted by nicotine, and were not affected by scaling.
Keywords: adverse effects; cotinine; fibroblast; nicotine